Preferences of Accountancy Graduating Students of a CPA Review Center: A Conjoint Analysis Study - Rey Castillo; Enrico C. Yee, Jr. (Jurnal Bisnis dan Keuangan, 2023)
Conjoint Analysis was used in this study to ascertain the preferences of accountancy graduates from a CPA review institution in Davao City. The study also established the aggregate model and the relative importance of the CPA review center characteristics, including track record, reviewers, conduciveness, review materials, and affordability in contributing to the overall value of review centers. Based on the results, "track record" is the most important attribute and "affordability" is the least important attribute, while other CPA review center attributes were also found important in determining the review centers' overall utility. On the aggregate level the preferred design model of the respondents is described by: (a) Track Record-produced board topnotchers/placers and has an above average national passing rate; (b) Reviewer-author of a book, a board placer and at least 15 years' experience as instructor; (c) Conduciveness- less than 50 reviewees in a room; (d) Review Materials-comprehensive review materials with three years recency; and (e) affordability-Php10,000 below.